VE‐PTP inhibition stabilizes endothelial junctions by activating FGD5. (14th May 2019) - Braun, Laura J; Zinnhardt, Maren; Vockel, Matthias; Drexler, Hannes C; Peters, Kevin; Vestweber, Dietmar
Abstract: Inhibition of VE‐PTP, an endothelial receptor‐type tyrosine phosphatase, triggers phosphorylation of the tyrosine kinase receptor Tie‐2, which leads to the suppression of inflammation‐induced vascular permeability. Analyzing the underlying mechanism, we show here that inhibition of VE‐PTP and activation of Tie‐2 induce tyrosine phosphorylation of FGD5, a GTPase exchange factor (GEF) for Cdc42, and stimulate its translocation to cell contacts. Interfering with the expression of FGD5 blocks the junction‐stabilizing effect of VE‐PTP inhibition in vitro and in vivo . Likewise, FGD5 is required for strengthening cortical actin bundles and inhibiting radial stress fiber formation, which are each stimulated by VE‐PTP inhibition. We identify Y820 of FGD5 as the direct substrate for VE‐PTP. The phosphorylation of FGD5‐Y820 is required for the stabilization of endothelial junctions and for the activation of Cdc42 by VE‐PTP inhibition but is dispensable for the recruitment of FGD5 to endothelial cell contacts. Thus, activation of FGD5 is a two‐step process that comprises membrane recruitment and phosphorylation of Y820. These steps are necessary for the junction‐stabilizing effect stimulated by VE‐PTP inhibition and Tie‐2 activation. Synopsis: Inflammation‐induced vascular permeability is suppressed by inhibiting the endothelial tyrosine phosphatase VE‐PTP. FGD5, a GEF for Cdc42, is essential for this effect and acts as a direct substrate of VE‐PTP, which stabilizes endothelial junctions. FGD5 tyrosine phosphorylation is essential for endothelial junction stabilization. VE‐PTP inhibition activates FGD5 in two steps: by Tie‐2, Rap‐1 dependent junction recruitment and by phosphorylation of Y820. FGD5 supports cortical actin and inhibits radial stress fibers by activating Cdc42 and Rac1. Abstract : Inflammation‐induced vascular permeability is suppressed by inhibiting the endothelial tyrosine phosphatase VE‐PTP. FGD5, a GEF for Cdc42, is essential for this effect and acts as a direct substrate of VE‐PTP, which stabilizes endothelial junctions.